I Never Thought I Would End Up Here: the Context of Nursing Home Relocation Among Lithuanian Older Adults - Charenkova, Jūratė (Socialinė teorija, empirija, politika ir praktika, 2023)
Nursing home relocation is considered one of the most significant and stressful events in older age. Research shows that a variety of factors influence the decision to move to a nursing home and that the circumstances of the move have an impact on the post-move adaptation process and the quality of life in the nursing home. This paper aimed to reveal the context of the nursing home relocation of older people. Research data was gathered through life story interviews with 18 nursing home residents. Life story interviews were supplemented with semi-structured interview questions.The research revealed that the decision to move and the subjective experience of nursing home relocation is shaped not only by micro-environmental factors of an older person, such as health status or certain personality traits, but also by the conditions of the broader socio-economic, political and historical context. The interaction of these factors, which can be conditionally distinguished at the individual, family (community) and societal levels, creates a unique context in which older people decide to move to a nursing home.On an individual level, such factors as a person’s health, values and beliefs, personality traits, circumstances of the nursing home relocation and knowledge of possible alternatives to residential care affect the relocation decision-making. On the family or community level, the influence of family members, recommendations from social workers, doctors and acquaintances, community social support networks and access to social services play an important role. And lastly, on the societal level such factors as cultural norms and values (i.e. societal attitudes towards residential care and attitudes towards parental care), organisation of the social services system and history of the country (Soviet era) affect the nursing home relocation decision-making.
Keywords: residential care; older people; decision to move to a nursing home; nursing home relocation; well-being